2000
DOI: 10.1074/jbc.m004985200
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Selenocysteine for Catalytic Cysteine 41 Enhances Enzymatic Activity of Plant Phospholipid Hydroperoxide Glutathione Peroxidase Expressed in Escherichia coli

Abstract: The citrus phospholipid hydroperoxide glutathione peroxidase (cit-PHGPx) was the first plant peroxidase demonstrated to exhibit PHGPx-specific enzymatic activity, although it was 500-fold weaker than that of the pig heart analog. This relatively low activity is accounted for the catalytic residue of cit-PHGPx, which was found to be cysteine and not the rare selenocysteine (Sec) present in animal enzymes. Sec incorporation into proteins is encoded by a UGA codon, usually a STOP codon, which, in prokaryotes, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 37 publications
6
42
0
1
Order By: Relevance
“…E. coli lacks GPx-1 and PHGPx-like activities (25), and the negligible PHGPx activity that we detected in crude lysates from control cells transformed with empty vector was consistent with this. Cells overexpressing GPX1, GPX2, and GPX3 exhibited PHGPx-like activities that were ϳ4-, 8-, and 11-fold higher than background, respectively (Fig.…”
Section: The Peptide Sequences Encoded By Gpx1 Gpx2 and Gpx3supporting
confidence: 69%
“…E. coli lacks GPx-1 and PHGPx-like activities (25), and the negligible PHGPx activity that we detected in crude lysates from control cells transformed with empty vector was consistent with this. Cells overexpressing GPX1, GPX2, and GPX3 exhibited PHGPx-like activities that were ϳ4-, 8-, and 11-fold higher than background, respectively (Fig.…”
Section: The Peptide Sequences Encoded By Gpx1 Gpx2 and Gpx3supporting
confidence: 69%
“…It has been shown that fusion of SECIS elements to its appropriate location in mRNA of proteins to which a UGA codon was introduced in the open reading frame resulted in the incorporation of Sec. This has been shown both in mammalian proteins (51,52) and in bacteria (53). However, we could not identify a typical eukaryotic secondary structure in the 0.9-kb 3Ј-UTR sequence of Crgpx mRNA (Vienna RNA Package, version 1.4; Ref.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, recombinant selenoprotein production is difficult, with the main barrier being a proper interaction between E. coli SelB and a given selenoprotein mRNA (12,13,21,43). Insertion of selenocysteine at a specific site into a protein can be achieved only by using a hairpin structure which strongly resembles the fdhF SECIS element at a proper distance downstream of a UGA codon (3,7,16,18). However, sequence requirements for the SECIS element would usually result in amino acid changes in the respective protein.…”
mentioning
confidence: 99%